Hepatobiliary System Involvement in Neonatal Sepsis: A Clinical and Morphological Study - Bakhronovna, Bakhshilloeva Rano; Bakhshillaevna, Juraeva Gulbahor (American Journal of Biomedicine and Pharmacy, 2026)
Neonatal sepsis remains a leading cause of mortality in the neonatal period and is frequently accompanied by multiple organ dysfunction. The hepatobiliary system plays a crucial role in metabolic regulation, immune response, and detoxification; therefore, its involvement reflects the severity and systemic nature of septic injury. However, clinical and morphological characteristics of hepatobiliary damage in neonatal sepsis have not been sufficiently systematized.